2012
DOI: 10.1590/s0100-29452012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Predição simultânea dos efeitos de marcadores moleculares e seleção genômica ampla em cajueiro

Abstract: RESUMO -A seleção genômica ampla (genome wide selection -GWS) foi proposta como uma forma de aumentar a eficiência e acelerar o melhoramento genético, enfatizando a predição simultânea dos efeitos genéticos de grande número de marcadores genéticos de DNA dispersos em todo o genoma de um organismo, de forma a capturar os efeitos de todos os locos e explicar a variação genética de um caráter quantitativo. Objetivou-se com o presente trabalho aplicar o princípio da GWS no melhoramento do cajueiro, estimando simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
2
3
0
1
Order By: Relevance
“…However, when the optimal number of markers was reached, which maximizes the r gg estimates, the selective accuracy decreased with the increase in the number of markers. Results were similar to those of other researchers (Fernando et al, 2007; Cavalcanti et al, 2012), where the increase in the number of markers did not show a linear relationship with the accuracy of the GS. Studies with simulated data have demonstrated that the use of a large number of markers led to a reduction in the limitation imposed by the small size of the training population (Resende, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, when the optimal number of markers was reached, which maximizes the r gg estimates, the selective accuracy decreased with the increase in the number of markers. Results were similar to those of other researchers (Fernando et al, 2007; Cavalcanti et al, 2012), where the increase in the number of markers did not show a linear relationship with the accuracy of the GS. Studies with simulated data have demonstrated that the use of a large number of markers led to a reduction in the limitation imposed by the small size of the training population (Resende, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The results for ha2 and r gy showed a high positive association, with a correlation coefficient of 88%. As observed in this work, the association between predictive capacity and heritability has been reported by other researchers (Cavalcanti et al, 2012; Gois et al, 2016). Prediction bias for most of the evaluated traits showed a b estimate close to the unit.…”
Section: Discussionsupporting
confidence: 89%
“…However, when the genetic effects were estimated and the GV was predicted within each family (for large families), the accuracy was satisfactory, as seen by the results presented here. Cavalcanti et al (2012) confirmed that within families, GWS is an interesting alternative that can be used to increase the breeding efficiency of cashew. In that study, the authors obtained a high accuracy value (0.86) for a characteristic with high heritability with only 74 individuals and a limited number of markers (238).…”
Section: Genetics and Molecular Research 15 (4): Gmr15048863mentioning
confidence: 54%
“…I.B. Gois et al The predictive ability of GWS, which reflects the ability of molecular information to consistently predict a phenotype (Cavalcanti et al, 2012), ranged from 0.53 for the ratio of soluble solids/acidity and soluble solids traits, to 0.64, for the longitudinal diameter of fruit, fruit mass, and number of fruits per box (Table 1). These magnitudes are similar to those reported for forest trees species , Resende Junior et al, 2012 and dairy cattle breeding (Hayes et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Já a matriz proposta por Yang et al (2010) (matriz de parentesco unificado) foi proposta para o estudo do caráter peso de humanos, em uso para associação de marcas significativamente associadas com o fenótipo (Genome-wide association study -GWAS) na ocasião. Este mesmo autor propôs um ajuste nesta matriz de parentesco unificado por meio de um coeficiente de regressão estabelecido empiricamente, objetivando explicar a herdabilidade total estimada (componentes aditivos e não aditivos) a partir da captura de marcadores de pequenos efeitos em desequilíbrio de ligação com alelos relacionados à variável causal estudada, peso em humanos, levando em consideração o MAF (Minor allele frequency) de ambos (YANG et al, 2010 O procedimento BLUP permite a utilização de todos os efeitos (fixos e aleatórios) do modelo estatístico, da covariância genética entre os indivíduos ou genitores em avaliação, ponderar aqueles genótipos com desigual número de observações na mesma ou em diferentes gerações e, assim, maximizar a acurácia, a qual depende basicamente da proporção entre a variação residual média e a variação genotípica, sendo que a variação residual média depende do número de repetições (RESENDE;DUARTE, 2007;CAVALCANTI;RESENDE, 2012 (MEYER, 1989;JOHNSON;THOMPSON, 1995;FALCÃO et al, 2009;MENEZES et al, 2013) e vegetal (BERNARDO, 1995BAUER et al, 2006;NUNES et al, 2008 Portanto, baseando-se nestes conceitos, é possível construir estruturas de matrizes de variância-covariância de parentesco que estejam de acordo com as pressuposições da genética quantitativa e do modelo estatístico-genético adotado (YANG et al, 2010).…”
Section: Effect Of Markers Density and Type Of Genomic Relationship Munclassified